THE COMPREHENSION OF INTERNATIONAL PHONETIC ALPHABET ROLE TOWARDS ENGLISH LEARNERS' PRONUNCIATION IN ACHIEVING SUCCESSFUL ORAL COMMUNICATION - Muhammad Yasminto (Konsorsium Dosen Sekolah Tinggi Agama Islam (STAI) Al-Yasini Pasuruan, 2020)
Abstract The article aims to find out the comprehension of the International Phonetic Alphabet role after the students had learned the phonology and phonetics materials in “Introduction to Linguistics” course. Qualitative approach was conducted to answer the problem of this study. To collect the data, the researcher used closed questionnaires to the 2nd semester students of English Study Program of Hasanuddin Islamic High School, Pare-Kediri in the academic year 2019/2020. The results of this study indicates that respondents have the same comprehension after being assisted by phonology and phonetics materials in improving their pronunciation errors. They were able to read phonetics transcription through phonetics dictionary application called with toPhonetics and increase confidence when pronouncing the words. They increasingly realized the importance of International Phonetic Alphabet in English pronunciation, so that they had the ability to read phonetics dictionary easily. It was proved from 22 respondents answering eight points related to the instrument that the average percentage in the strong agreement was 50%, mild agreement was 44%, less agreement was 7,5%, and disagreement was 0%. So, it can be concluded that the students have the same comprehension of International Phonetic Alphabet role to reduce errors in pronouncing the words to achieve successful oral communication. Keywords: International Phonetic Alphabet, English Pronunciation, Oral